(untitled) (Vietnam Journal of Community Medicine, 2026)
ABSTRACT Objective: To describe the clinical characteristics and evaluate the surgical outcomes of local flap reconstruction for cheek soft tissue defects at Viet Tiep Friendship Hospital. Methods: A retrospective case series study was conducted on 20 patients with cheek soft tissue defects treated with local flaps from January 2022 to December 2024. Data were collected from medical records, including clinical characteristics, surgical techniques, and treatment outcomes. Outcomes were assessed at two time points: 2 weeks and 3 months postoperatively. Results: The mean age was 44.2 ± 12.8 years, with males accounting for 55%. The main causes of defects were tumor excision (55%) and trauma (35%). Defects smaller than 3 cm accounted for 70% of cases. V–Y advancement flaps were the most commonly used (40%), followed by rotation flaps and transposition flaps (30% each). The complete flap survival rate was 95%, with one case (5%) of partial necrosis and no cases of total necrosis. At 3 months, 90% of patients achieved good aesthetic and functional outcomes. The overall patient satisfaction rate was 85%. Conclusion: Local flaps can be a safe and effective method for reconstructing cheek soft tissue defects, providing favorable aesthetic and functional outcomes. Appropriate flap selection based on defect size and location plays a key role in optimizing treatment results.